Inter-temporal savings, current account trends and asymmetric shocks in a heterogeneous European Monetary Union - Gunther Schnabl; Holger Zemanek (Intereconomics, 2011)
This paper contributes to the discussion on the European current account imbalances by analysing the intra-European trends since 1990 based on the theory of optimum currency areas. The authors show that German unification was the origin of not only the 1992-93 EMS crisis but also rising intra-European current account imbalances since 1999 that led to the European debt crisis. They argue that a reduced German current account surplus is in the interest of German taxpayers to contain financial risk, but that it would also impose austerity on the rest of Europe unless money supply expands even further.
Keywords: 330